Rabin-p encryption scheme analysis on MQTT - Che Izam, Wan Abdullah; Syed Adnan, Syed Farid; Asbullah, Muhammad Asyraf (IEEE, 2023)
This paper presents a Rabin-P Encryption Scheme Analysis on Message Queuing Telemetry Transport (MQTT), where MQTT is one of the OASIS standard messaging protocols used for the Internet of Things (IoT). MQTT is very popular since it has a light footprint on energy consumption and computation. MQTT payloads are not secure by default unless all the links are encrypted by Secure Sockets Layer (SSL)/Transport Layer Security (TLS). However, all clients and brokers must install certificates to use SSL/TLS. Another way, the payloads can be encrypted with an encryption scheme to provide end-to-end without having to conFigure all the client and broker. Therefore, an encryption scheme known as Rabin-p is introduced to MQTT payloads. In this work, a microprocessor selected Raspberry Pi 4. Then, an analysis is conducted on MQTT with the Rabin-p scheme to analyze the encryption and decryption runtime of the Rabin-p encryption scheme on MQTT and the energy usage of the Rabin-p encryption scheme on MQTT. Although asymmetric encryption provides higher security, it requires an expensive calculation that leads to higher energy usage. However, Rabin-p offers a lower processing algorithm. A conclusion can be made that using Rabin-p in MQTT can help improve the payload security since Rabin-p offers a complex algorithm which is it harder to decrypt the messages when communicating between devices. Rabin-p can also be integrated with MQTT Mosquitto since it uses minimal energy.